1992
DOI: 10.1111/j.1744-7348.1992.tb03471.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between species of Trichodorus and Paratrichodorus vector nematodes and serotypes of tobacco rattle tobravirus

Abstract: SummaryVirus transmission bait tests with single trichodorid nematodes from England, the Netherlands, Scotland or Sweden showed that a substantial degree of specificity occurs between trichodorid vector species and tobravirus serotypes. This specificity was more apparent with associations between Paratrichodorus vector species and tobravirus serotypes than with those between Trichodorus species and tobravirus serotypes. P. pachydermus transmitted PRN‐serotype tobacco rattle virus (TRV) isolates, P. teres ORE‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 20 publications
4
41
0
Order By: Relevance
“…For each of the reconstituted 'parent' combinations (B1B2 and K1K2) one single lesion isolate, and for each of the two pseudorecombinants four single lesion isolates (B1K2~d and K1B2~a ), were propagated in N. clevelandii. The eight selected pseudorecombinant isolates (B1K2~a, K1B2~_o), the reconstituted isolates (B1B2 and K1K2) and isolates PPK20 and PLB all gave positive reactions in F(ab')2-ELISA (Barbara & Clark, 1982;Ploeg et al, 1992a) when virus particles were trapped with the F(ab')2 fragment and detected with y-globulin of PRN antiserum (A4ossample/A4o~healthy > 4). However, when monoclonal antibody SCR81, which was prepared using isolate PLB as immunogen (F. J. Legorburu, personal communication), was used instead as the detecting antibody (in tissue culture fluid, diluted 1/30), only the four K1B2 pseudorecombinant isolates, the reconstituted isolate B1B2 and isolate PLB gave positive reactions (A4ossample/A~o~healthy > 10), whereas the four B1K2 pseudorecombinant isolates, the reconstituted K1K2 isolate and isolate PPK20 failed to react (A~ossample/A4o~healthy < 1.5).…”
Section: Rna-2 Of Tobacco Rattle Virus Encodes the Determinants Of Trmentioning
confidence: 99%
See 2 more Smart Citations
“…For each of the reconstituted 'parent' combinations (B1B2 and K1K2) one single lesion isolate, and for each of the two pseudorecombinants four single lesion isolates (B1K2~d and K1B2~a ), were propagated in N. clevelandii. The eight selected pseudorecombinant isolates (B1K2~a, K1B2~_o), the reconstituted isolates (B1B2 and K1K2) and isolates PPK20 and PLB all gave positive reactions in F(ab')2-ELISA (Barbara & Clark, 1982;Ploeg et al, 1992a) when virus particles were trapped with the F(ab')2 fragment and detected with y-globulin of PRN antiserum (A4ossample/A4o~healthy > 4). However, when monoclonal antibody SCR81, which was prepared using isolate PLB as immunogen (F. J. Legorburu, personal communication), was used instead as the detecting antibody (in tissue culture fluid, diluted 1/30), only the four K1B2 pseudorecombinant isolates, the reconstituted isolate B1B2 and isolate PLB gave positive reactions (A4ossample/A~o~healthy > 10), whereas the four B1K2 pseudorecombinant isolates, the reconstituted K1K2 isolate and isolate PPK20 failed to react (A~ossample/A4o~healthy < 1.5).…”
Section: Rna-2 Of Tobacco Rattle Virus Encodes the Determinants Of Trmentioning
confidence: 99%
“…Brown et al (1989a) and Ploeg et al (1992a) reported that different trichodorid species were associated with serologically distinct TRV isolates. Ploeg et al (1992b) subsequently demonstrated that initially virus-free Paratrichodorus pachydermus successfully acquired and transmitted only TRV isolates belonging to the PRN serotype, with which this vector species was associated in the field.…”
Section: Rna-2 Of Tobacco Rattle Virus Encodes the Determinants Of Trmentioning
confidence: 99%
See 1 more Smart Citation
“…In The Netherlands, Paratrichodorus teres, P. pachydermus and Trichodorus similis are the major vectors of TRV in flowerbulb growing areas (Ploeg et al, 1991). These vector species transmit serologically distinct isolates of TRV (Ploeg et al, 1992). Host finding by P. teres appears to be very effective.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the relative paucity of PEBV isolates described so far or it may be due to a more fundamental property of the viruses. In this paper, we report the construction of an infectious cDNA clone of RNA2 of TRV isolate PPK20 (Ploeg et al, 1992 ;Hernandez et al, 1995) and the generation of hybrids between this clone and an infectious clone of PEBV RNA2 (MacFarlane et al, 1996). Experiments were carried out to compare the ability of TRV RNA1 and PEBV RNA1 to replicate hybrid RNA2 molecules containing heterologous 5h-terminal or 3h-terminal regions.…”
mentioning
confidence: 99%